Analyzing and Choosing the Appropriate Model for Issuing Islamic Securities for Financing SMEs - Mohammad Mahdi Faridouni; Mohammad Tohidi; Milad Isaei (تحقیقات مالی اسلامی (پیوسته))
Financing has always been one of the main challenges of SMEs in Iran. Therefore, developing financial instruments for these companies and reducing their dependence on bank financing is always one of their essential needs. Despite the development of the Sukuk market in recent years, the capacity of this market has not been provided for SMEs. This article seeks to provide an optimal model for financing SMEs. The present research is considered to be mixed (qualitative-quantitative) from the point of view of the applied goal and qualitative-quantitative from the point of view of the nature of the data and descriptive-survey from the point of view of the data collection method. In order to design a suitable model, first, in interviews with experts in the field of financing SMEs, as well as available resources, the financing challenges of these companies were analyzed. In the next step, based on two assumptions, 7 models were designed for issuing Sukuk. Then, based on the TOPSIS method, these models were prioritized and Wakalah model is choosed.